Enhancing Conceptual Understanding of Plant Classification through Mobile-Based Interactive Plant Tagging in Outdoor Biology Education - Salsabila, Almirah Faisa; Hidayat, Muhammad Luthfi (Universitas Muhammadiyah Surakarta, 2025)
According to a report from the ministry of education, culture, research, and technology (2022), only 41% of junior high school students reached the minimum completeness criteria score in science subjects, with the botany subtopic being one of the lowest levels of understanding. This study aims to determine the effect of using interactive media based on Mobile Plant Tagging in outdoor learning on students' concept understanding on the material of differences between dicotyledonous and monocotyledonous plants. The research method used was quantitative with a quasi-experimental design. The sample consisted of two experimental classes and one control class using random sampling techniques. Pretest and posttest data were analyzed using the t-test (Independent Sample T-test) to measure students' conceptual understanding. The results showed a significant increase in posttest scores in the experimental group compared to the control group. The learning approach that combines direct interaction with real objects and mobile-based technology support is proven to be able to improve students' concept understanding, active participation, and learning motivation. These findings indicate that Mobile Plant Tagging media is effective as an innovative learning strategy in improving science literacy in a contextual and applicable manner.